Analysis of the Impact After the Covid-19 Pandemic on the Development of MSMEs in Indonesia - Kumba Digdowiseiso; Hamrin Hamrin (Budapest International Research and Critics University, 2022)
The existence of the covid-19 endemic is a lot of consequences experienced by the ruler, especially even small residents. This research intends to make 1) Analyze the endemic consequences of MSME zone actors; 2) Analyze the application of the ruler's wisdom to MSME actors affected by endemics; 3) Analyze the self-adjustment strategies that MSME actors try after endemic. This research uses descriptive qualitative procedures in which researchers want to find information related to research. The results show that MSME actors are very affected by the presence of covid-19 endemics, especially the efforts of the inferior desire zone that face shrinkage in turnover, but in other parts the number of MSMEs increases in the era of covid-19 endemic; not only that, the central Ruler also distributed encouragement in the form of a Productive Banpres of Micro-Efforts (BPUM) to the actors of micro-efforts.